Answer:
2x - 4
Step-by-step explanation:
2(3x + 6) = 6x + 12
2(-2x - 8) = -4x -16
6x + 12 - 4x - 16 = 2x - 4
Hi,
Answer:
48 cm
Step-by-step explanation:
14 + x = 62
62 - 14 = 48
x = 48 cm
Have a good one!
Since you've told us that this is an isosceles triangle, we know that the 'legs' have equal length. So we can write
x + 1 = -x + 7
Add 'x' to each side: 2x + 1 = 7
Subtract 1 from each side: 2x = 6
Divide each side by 2 : x = 3
Now, if the length of the base is 3x - 3 ,
that length is
3(3) - 3 = 6 .
Answer:
= 1/8 or 0.125
Step-by-step explanation: